Ensayos sobre Derecho civil patrimonial y no patrimonial -Doctrina, jurisprudencia y análisis normativo- - Castilla Colquehuanca, Jhoni Shang (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
It is known that Law, from an epistemological point of view, is not only a theoretical career but also a practical one, since it is oriented and finds its application in social relations, since it is always created and ultimately referred to, to a precise ontological reality, that is, the human being (subject of law).